2020
DOI: 10.29244/jitkt.v12i3.32013
|View full text |Cite
|
Sign up to set email alerts
|

Klasifikasi Habitat Perairan Dangkal Dari Citra Multispasial Di Perairan Pulau Kapota Dan Pulau Kompoone, Kepulauan Wakatobi

Abstract: Habitat perairan dangkal sangat penting dipetakan diantaranya karena: (1) mendukung perencanaan, manajemen, dan pengambilan keputusan tata ruang pemerintah; (2) mendukung dan mendesain Marine Protected Area (MPA); (3) melakukan program penelitian ilmiah yang bertujuan untuk menghasilkan pengetahuan tentang ekosistem bentik dan geologi dasar laut; (4) melakukan penilaian sumber daya dasar laut yang hidup dan tidak hidup untuk tujuan ekonomi dan menajemen, termasuk rancangan cadangan perikanan. Hingga saat ini b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In comparison to these studies, the accuracy of the maps in this study was found to be similar to those that produced benthic habitat maps with 8 to 9 benthic habitat classes. It is worth noting that the accuracy of the resulting map decreases as the number of classified benthic habitat classes increases (Andréfouët et al 2003;Mastu et al 2018;Siregar et al 2020;Wicaksono et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to these studies, the accuracy of the maps in this study was found to be similar to those that produced benthic habitat maps with 8 to 9 benthic habitat classes. It is worth noting that the accuracy of the resulting map decreases as the number of classified benthic habitat classes increases (Andréfouët et al 2003;Mastu et al 2018;Siregar et al 2020;Wicaksono et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This technology is employed for assessing natural resources in terrestrial sites, such as mangroves (Valderrama-Landeros et al 2018;Hamuna et al 2019b;Ghorbanian et al 2021;Maurya et al 2021) as well underwater resources like coral reefs and seagrass beds (Zhou et al 2018;Wilson et al 2019;Fauzan et al 2021;Lizcano-Sandoval et al 2022;Rosalina et al 2023;Satya et al 2023). The advancement of satellite remote sensing technology has been rapid (Nguyen et al 2021), demonstrated by the development of satellite sensors capable of detecting shallow waters based on specific characteristics (Siregar et al 2020). The development of multi-and hyper-spectral sensors has improved the spatial detail of satellite images, along with the advancements in satellite image data processing.…”
Section: Introductionmentioning
confidence: 99%